Knowledge of Diabetes Mellitus among Pregnant Women in Three Districts of Nepal - Shrestha, S; Thapa, P; Saleh, F; Thapa, N; Stray-Pedersen, B; Khanom, K (Journal of Nepal Health Research Council, 2014)
Background: Diabetes mellitus is an emerging health problem in developing world with the consumption of energy dense diet and inactive lifestyle. The problem of diabetes is further expanded due to ignorance and lack of knowledge. The aim of the study was to assess the knowledge of diabetes among pregnant women in three districts of Nepal. Methods: A community based cross-sectional study was conducted in three districts in mountain, hilly and plain areas of Nepal. A total of 590 pregnant women were interviewed during the period of July 2009 to June 2010. A knowledge score system was applied. Poor score was <40%, average (40-60%) and good (>60%) of the total score. Statistical software SPSS 11.5 was used for data entry, data management and analysis. Results: Out of 590 pregnant women, only 41% had heard about diabetes mellitus. Majority of the participants (75%) from age group >30 years had not heard about diabetes. Among the 241 with some knowledge, the knowledge score median percent(range) on the meaning, symptoms, risk factors, treatment, prevention, complications and overall knowledge were 50%(0-100), 25% (0-75), 20% (0-60), 20% (0-100), 25% (0-100), 20% (0-60) and 26% (0-58) respectively. According to defined category, majority of those who ever heard about diabetes had poor knowledge (95%). Knowledge among literate women (p=.001), women residing in Kailali district (plain region) (p=.003) and those with positive family history of diabetes (p=.003) was found to be significant. Conclusions: As large proportions of Nepalese pregnant women do not have any knowledge or have poor knowledge regarding diabetes, extensive health education and health promotion programs are urgently recommended to prevent diabetes in Nepal. Keywords: diabetes mellitus; knowledge.